The Comparison of Tannin Fractions in Calliandra calothyrsus Leaves Utilizing Butanol-HCl4 and Protein-Precipitation Methods - Subagyo, Yusuf; Sumaryadi, Mas Yedi; Ifani, Merryafinola; Widodo, Hermawan Setyo; Yusan, Rizak Tiara (Universitas Jenderal Soedirman, 2024)
ABSTRACT. Butanol-HCl4 (Bu-HCl4) and Protein-Precipitation (P-P) are methods that proposed to determine the content of free tannins, protein-bound tannins, and fiber-bound tannins. This study aims to determine the feasibility of tannin measurements by both methods and validation of Analytical Methods (VMA) evaluates specific parameters like accuracy, precision, specificity, and linearity through lab testing. The material used was twenty C. calothyrsus leaves which collected randomly from different trees. The samples were measured by both methods in triplicates for qantification and validation. The obtained data were analyzed by descriptive and t-test to compare both methods. The analysis of VMA shows that the P-P method yields higher accuracy compared to the Bu-HCl method in percentage recovery rates. The quantification of free tannins, protein-bound tannin, tannin fiber, and total tannin by the Bu-HCl4 method versus the P-P method showed significantly higher values (p<0.01) for the Bu-HCl4 method: free tannins (13.44±0.54 vs. 7.11±0.16), protein-bound tannin (2.80±0.44 vs. 1.52±0.20), tannin fiber (5.20±0.45 vs. 1.00±0.21), and total tannin (21.50±0.88 vs. 9.59±0.36). The methode validation result of Bu-HCl4 and P-P methods in the accuracy was different, but the linearity test showed a good response. In conclusion, the tannin quantivication by the P-P and Bu-HCl4 can be applied for C. calothyrsus analysis. The total tannin content was higher if quantified by the Bu-HCl4 method compared to P-P. The accuracy of the P-P found higher than the Bu-HCl4 method. Keywords: Butanol-HCl4, leaves C. calothyrsus, protein-precipitation methods, tannin.